2022
DOI: 10.1038/s41598-021-04170-2
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing performance and yield of vertical GaN diodes using wafer scale optical techniques

Abstract: To improve the manufacturing of vertical GaN devices for power electronics applications, the effects of defects in GaN substrates need to be better understood. Many non-destructive techniques including photoluminescence, Raman spectroscopy and optical profilometry, can be used to detect defects in the substrate and epitaxial layers. Raman spectroscopy was used to identify points of high crystal stress and non-uniform conductivity in a substrate, while optical profilometry was used to identify bumps and pits in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Third, the experiment contained thousands of samples, which is enough to see if there is a trend, but typically millions are required to train a model suitable for commercial manufacturing. Fourth, our previous research 33 has shown that many benign defects are present as shown by the cluster plots in Fig. 5 from the large number of points at approximately 0.1% outlier area and an RMS roughness of approximately 5 nm.…”
Section: Discussionmentioning
confidence: 86%
“…Third, the experiment contained thousands of samples, which is enough to see if there is a trend, but typically millions are required to train a model suitable for commercial manufacturing. Fourth, our previous research 33 has shown that many benign defects are present as shown by the cluster plots in Fig. 5 from the large number of points at approximately 0.1% outlier area and an RMS roughness of approximately 5 nm.…”
Section: Discussionmentioning
confidence: 86%
“…The GaN samples investigated were 500 nm thick p-type (Mg dopant) layers epitaxially grown via metal-organic chemical vapor deposition (MOCVD) on an 8 µm thick unintentionally doped (UID) buffer layer on an n-type GaN substrate 16,17 . The samples were coated in photoresist for transport.…”
Section: Gan Samplesmentioning
confidence: 99%
“…Elimination of dislocations is crucial for device reliability, as dislocations in the substrate are known to propagate through the epitaxial growth, compromising the active device layers 11,12 . For example, substrates with patterned arrays of dislocation centers exhibit spatially-varying device performance and failure locations [13][14][15][16][17] . However, direct correlation between defective substrate areas, dislocations, and device performance is not straightforward: certain defects appear to be more harmful for devices than others 11,12,16,17 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, lateral devices are limited to low-to medium-voltage applications (less than 1 kV). On the other hand, vertical geometry devices offer several advantages over lateral devices, such as better scaling factors and thermal management, a higher critical electric field and breakdown voltage, and better radiation tolerance [9,10]. Several studies have reported the attractive performance of vertical GaN-on-GaN p-n diodes, which have a high breakdown voltage (4-6 kV) [11][12][13] and low specific on-resistance (less than 0.5 mΩ cm 2 ) [10,14].…”
Section: Introductionmentioning
confidence: 99%